Central Sharia Board and Mechanism of Sharia Supervision in Islamic Banks; Emphasizing International Standards and Countries' Experiences - Leila Mehrabi (تحقیقات مالی اسلامی (پیوسته))
Failure to comply with the rules and principles of sharia poses risks in the banking system. In this regard, in addition to sharia supervision standards issued by international institutions, each of the countries involved in Islamic finance, while considering the variety and level of their specializations, has determined a solution to ensure compliance with shariah when dealing with Islamic financial and banking products. Hence, the high significance of improving sharia supervision and the need to form sharia supervisory boards in the Central Bank and other Islamic banks to ensure sharia compliance of their activities and products. This research, after stating the importance of sharia risk and sharia supervision in Islamic banks, has identified the standards published by the most important international institutions such as the Islamic Financial Services Board (IFSB) and the Accounting and Auditing Organization of Islamic Financial Institutions (AAOIFI) in the field of sharia supervision, and investigated the experiences of different countries in that regard. Finally, some suggested solutions for strengthening sharia supervision of the countries’ banking system have been presented. The results show that in most countries, each Islamic financial institution is required to form an internal Sharia Supervisory Board (SSB) to ensure compliance of banking operations with sharia principles, and in some others, they have created a higher sharia authority at the supervisory level, such as the Central Bank, which, by standardizing and integrating Islamic rules and laws, plays an important role in ensuring sharia compliance of their activities.